Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1055/s-2006-932181
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of 18F-Fluorodeoxyglucose PET for Radiosurgery Planning and Response Monitoring in Patients with Recurrent Spinal Metastasis

Abstract: To our knowledge, this is the first report using FDG-PET with radiosurgery in patients with recurrent spinal metastases hidden under metallic artifacts. The mass responses measured by SUV changes in FDG-PET correlated with the clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…SUV max in this context is the value limited to the most active voxel and is highly reproducible across observers. In breast cancer patients with disseminated bone metastases the change in pre- to posttreatment SUV values correlated strongly with both clinical response and percentage change in tumour marker value [97] , with 30–54% decreased values in responding sites versus marginally or unchanged values in nonresponding lesions [98] . The parameter K i indicates regional clearance of [ 18 F] fluoride from blood plasma to bone mineral and was shown to be three times higher in metastatic lesions compared with adjacent unaffected bone [78] .…”
Section: Clinical Imagingmentioning
confidence: 93%
“…SUV max in this context is the value limited to the most active voxel and is highly reproducible across observers. In breast cancer patients with disseminated bone metastases the change in pre- to posttreatment SUV values correlated strongly with both clinical response and percentage change in tumour marker value [97] , with 30–54% decreased values in responding sites versus marginally or unchanged values in nonresponding lesions [98] . The parameter K i indicates regional clearance of [ 18 F] fluoride from blood plasma to bone mineral and was shown to be three times higher in metastatic lesions compared with adjacent unaffected bone [78] .…”
Section: Clinical Imagingmentioning
confidence: 93%
“…In the first instance, we have looked for a better characterization of the CTV with the assistance of functional imaging with FDG-PET/CT and F-DOPA-PET/CT. The literature suggests that the sensitivity of FDG-PET in detecting spinal metastases is high [14], but only one study evaluated the usefulness of FDG-PET/CT for radiosurgery planning in patients with recurrent spinal metastasis [15]. In our study, numerous vertebrae, judged pathological by MRI, were not detected by these techniques.…”
Section: Discussionmentioning
confidence: 59%
“…However, few studies on spinal intramedullary lesions have been reported. 5,6,8,11,13,[15][16][17]18 Although the majority of previously published studies are illustrative case reports, the findings suggest that spinal PET may play a role in the clinical diagnosis of spinal intramedullary lesions by helping to identify diagnostically troublesome lesions based on metabolic activity. Wilmshurst et al conducted a prospective study to investigate the use of FDG-and MET-PET for detection of spinal intramedullary tumors in 14 patients over a 5-year period.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,7,10,20,22,23 However, investigations of spinal intramedullary tumors using PET remain sporadic, with only case reports or case series available to date. 5,6,8,11,13,[15][16][17]18 PET diagnosis of spinal intramedullary tumors can- 18 F]-fluorodeoxyglucose (FDG)-PET/CT was performed in 26 patients with spinal intramedullary lesions. The region of interest (ROI) within the spinal cord parenchyma was placed manually in the axial plane.…”
mentioning
confidence: 99%